1997
DOI: 10.1111/j.0022-3646.1997.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Light‐dependent Growth, Dark Survival, and Glucose Uptake by Cryptophytes Isolated From a Freshwater Chemocline

Abstract: Clones of Cryptomonas phaseolus Skuja, Cryptomonas rostratiformis (Skuja) Skuja in Huber-Pestalozi, and Cryptomonas undulata Geruais were isolated from the deep chlorophyll maximum near the oxic/anoxic bounda7y layer of the mesoeutrophic lake Schlachtensee, Germany. Different autecologzcal features of these species were studied in batch culture experiments. Cryptomonas cf: ovata Ehrenberg and Chroomonas sf. that never dominated in the deep chlorophyll layer were also isolated from Schlachtensee to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
73
2
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 55 publications
(52 reference statements)
6
73
2
1
Order By: Relevance
“…Cryptophytes and diatoms, the most abundant taxa in all experiments (Berger et al 2010;Lewandowska and Sommer 2010), showed the strongest response to warming. This is in agreement with physiological characteristics of these taxa (Gervais 1997;Litchman et al 2007). Both have high maximum growth and nutrient uptake rates and are able to outcompete other groups under nutrient replete conditions, which were the starting condition in all experiments.…”
Section: Discussionsupporting
confidence: 92%
“…Cryptophytes and diatoms, the most abundant taxa in all experiments (Berger et al 2010;Lewandowska and Sommer 2010), showed the strongest response to warming. This is in agreement with physiological characteristics of these taxa (Gervais 1997;Litchman et al 2007). Both have high maximum growth and nutrient uptake rates and are able to outcompete other groups under nutrient replete conditions, which were the starting condition in all experiments.…”
Section: Discussionsupporting
confidence: 92%
“…Gasol et al (1993) showed that C. phaseolus maintained a high population density in the metalimnion without any sign of bacterial ingestion. Gervais (1997) also showed that several species of Cryptomonas could grow without bacterial ingestion in lab-oratory cultures. Thus, phagotrophy by Cryptomonas seems not for acquisition of some substance essential to their growth.…”
Section: Discussionmentioning
confidence: 95%
“…Tranvik et al (1989) 1 Corresponding author. suggested that phagotrophy in Cryptomonas is induced by low light conditions but concluded that bacteria are not an important energy source for Cryptomonas because their specific ingestion rate for bacteria was very limited even under low light. In other studies, Cryptomonas did not show any indication of phagotrophy (Sanders et al 1989;Gasol et al 1993;Gervais 1997). It should be noted, however, that these studies examined phagotrophy under laboratory conditions, where light intensity was controlled artificially or in situ at an unspecific time during the day.…”
mentioning
confidence: 81%
“…According to the recommendations of Gervais (1997) to cultivate cryptophytes, no boron was added and the N source was ammonium chloride rather than sodium nitrate. This light intensity does not limit the growth of Cryptomonas spp.…”
Section: Cultivationmentioning
confidence: 99%
“…This light intensity does not limit the growth of Cryptomonas spp. (Gervais, 1997). Continuous light conditions were chosen to reduce possible diurnal effects on cell P pools.…”
Section: Cultivationmentioning
confidence: 99%